2009
DOI: 10.1007/s00428-009-0770-6
|View full text |Cite
|
Sign up to set email alerts
|

Claudins 1, 3, and 4 protein expression in ER negative breast cancer correlates with markers of the basal phenotype

Abstract: In the present study we investigated the protein expression of claudins 1, 3, and 4 and their relationship to clinical variables and outcome in a cohort of ER-ve and ER+ve human invasive breast cancers. Immunohistochemical analysis was performed on tissue microarrays representing a total of 412 tumors and interpretable data was derived from 314, 299, and 306 tumors for claudins 1, 3, and 4, respectively. In the ER+ve subset, 5%, 89%, and 52%, and in the ER-ve subset, 39%, 79%, and 79% of tumors stained positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 42 publications
8
92
4
2
Order By: Relevance
“…21 We could not identify such a correlation, since the majority of our cases comprised benign and negative HER-2 samples, concordant with the findings of Madan et al 12 Claudin-4 was found to correlate with HER-2 immunohistochemical expression in 299 cases of invasive ductal carcinoma, 20 but another report did not find this correlation in 412 tumors. 31 In our series, this correlation was also not found (P = 0.0734). It seems that the larger contingent of nonneoplastic cases impeded a more specific correlation between these two variables.…”
Section: Fra-1 Expression Was Always Evident Around Ductal Structurescontrasting
confidence: 55%
“…21 We could not identify such a correlation, since the majority of our cases comprised benign and negative HER-2 samples, concordant with the findings of Madan et al 12 Claudin-4 was found to correlate with HER-2 immunohistochemical expression in 299 cases of invasive ductal carcinoma, 20 but another report did not find this correlation in 412 tumors. 31 In our series, this correlation was also not found (P = 0.0734). It seems that the larger contingent of nonneoplastic cases impeded a more specific correlation between these two variables.…”
Section: Fra-1 Expression Was Always Evident Around Ductal Structurescontrasting
confidence: 55%
“…Several studies have shown the function of claudins in various cancers. For example, the role of Claudin-1 in tumorigenesis has been found, demonstrating that Claudin-1 may be an oncogenic or tumor-suppressing protein (Morohashi et al 2007;Blanchard et al 2009). Claudin-7 overexpression promotes the loss of tumor cell polarization and contributes to tumorigenesis (Darido et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that claudin-2 expression is specifically elevated in liver-aggressive breast cancer cells and promotes their ability to metastasize to the liver. There is precedence for the upregulation of specific claudins in breast cancer, including claudin-3 and -4, which have been correlated with the poor prognosis, basal breast cancer subtype (Blanchard et al, 2009;Kulka et al, 2009;Lanigan et al, 2009). Thus, the metastatic phenotype of breast cancer cells can be influenced by the specific claudin in question and the context in which it is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrate the loss of specific claudins during breast cancer progression, whereas others suggest that overexpression of particular claudins are associated with poor outcome in breast cancer patients (Martin and Jiang, 2009). For example, some breast cancers exhibit a loss of claudin expression, including claudin-1, -2 and -7 (Kominsky et al, 2003;Sauer et al, 2005;Tokes et al, 2005;Kim et al, 2008), whereas claudin-3 and -4 can be overexpressed in human breast cancers, particularly in the triple-negative subtype (Kominsky et al, 2004;Blanchard et al, 2009;Kulka et al, 2009;Lanigan et al, 2009). Although these studies, which are focused on claudin expression in the primary tumor, suggest that specific claudin proteins may fulfill tumor-suppressor or tumor-promoting roles in breast cancer, little is known regarding claudin expression in breast cancer metastases.…”
Section: Introductionmentioning
confidence: 99%